Facial Nerve Branching Pattern in the Parotid Region: A Cadaveric Study (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: The present study’s objective was to examine the parotid region’s facial nerve branching pattern.One of the 12 pairs of cranial nerves, the facial nerve (VII), travels through the stylomastoid foramen to the parotidarea. It then passes through the parotid gland’s posteromedial surface. The substance of the parotid gland has acomplicated branching pattern and divides into five terminal branches. The platysma and face muscles are innervatedby these branches. Based on the presence of anastomoses or communications between the terminal branches,its complicated branching pattern has been divided into many categories. Materials and Methods: Twenty-onecadaveric hemi faces were used as a sample, and the dissected specimen photos were photographed. The locationof the facial nerve division, its relationship to the retromandibular vein, and the number of divisions was alldocumented in the dissected specimens. Results and Discussion: For head-and-neck surgeons, the facial nerve’sbranching pattern is crucial. The safe removal of the parotid gland without causing facial nerve damage is key to thesuccess of the procedure. Conclusion: The success rate of parotid procedures will be impacted by understandingof potential anatomical variances. To minimize post-operative problems, medical staff must be aware of thesevariations.